Thermoelectric Applications of Low-Dimensional Carbon Nanostructures with Acoustically Mismatched Boundaries. Issue 204 (2nd January 2020) - Poddar, P.
Abstract: Thermoelectric applications of low-dimensional carbon nanostructures offer new ways to manipulate the electron and phonon properties of a given material. High-resolution Raman spectroscopy of ultra-thin silicon-on-insulator structures reveals multiple peaks in the spectral range from 50 cm −1 to 160 cm −1 . The peak positions are consistent with the theoretical predictions and indicate the confined nature of phonon-transport in thin films and superlattices with a finite acoustic mismatch between layers. This opens up a novel turning capability for optimization of the thermoelectric properties of low-dimensional structures.